Role of the WTO in Developing Economic Reforms and Performance of Francophone Africa - Gajdošová, Annamária (2017)
This Master thesis is aimed to provide a theoretical framework of the application of Special and Differential Treatment in the countries of Francophone Africa from time perspective. How did they evolve and what progress they generated in the last century. The first chapter is to mention the economic and political featurs of the Francophone Africa countries and to identify why the membership in the WTO is important for advancement that they were able to achieve during the last decades. The second chapter classifies the WTO pillars in providing economic cooperation for developing countries. This section also describes the special provisions of WTO giving developing and least developed countries exclusive unilateral rights. The third chapter distresses the implementation of the WTO trade development instruments in Francophone Africa. This section will acknowledge the significance of the The Bali Package and November 2014 decisions. What is more, it will present the implications of Special and Differential Treatement in two biggest countries of Francophone Africa: Mauritania and Tchad. Significant point of this Master Thesis is the need for greater cooperation, coordination, and coherence among all nations of Francophone Africa. The challenge for them is not to create a new mechanism, but to get all of the existing mechanisms to work together more effectively to achieve their common goal.